A STUDY OF THE DENOTATIVE AND CONNOTATOTIVE MEANINGS IN MANIL SURI’S THE DEATH OF VISHNU - Shailee Pandya (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2020)
Semantics studies the nature of relationship between the symbol and the referent. There are two types of meanings: Denotative and Connotative meaning. Denotative meaning is also known as cognitive, descriptive, referential or conceptual meaning. It is the essential, objective and invariable meaning of the word recorded in the dictionary. While connotative meaning is the unspoken, hidden meaning that gives a word more emotional impact. This paper aims to study how denotative meaning of a novel (The Death of Vishnu by Manil Suri) gives as clear point of view about the novel and enriches our level of understanding, on other hand the knowledge about denotative and connotative meaning helps us to understand literature through society or society through literature and gives us multiple interpretations of the same novel. Keywords: Semantics,Denotative meaning, Connotative meaning, multiple interpretations